Pengajuan Artikel Jurnal Analisis Pengembangan Bisnis Kafe District Resto & Bar Untuk Meningkatkan Daya Saing - Wijaya, Tommy Halim; Susanto, Eko Harry (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
District Resto & Bar is one of the public spaces which is one of the industries engaged in Restaurant and bar. The purpose of this study is to analyze external factors and internal factors in District Resto & Bar in developing business in order to improve competitiveness. The research aims to formulate a strategy to implement District Resto & Bar. The strategy formulation starts from the analysis of the internal environment, external environment and industry environment of business, then using IFE matrix and EFE matrix scores to determine the position of District in IE matrix. The purpose is finding a suitable strategy to be implemented for District. The result of the IE matrix shows that café is at quandrant V “Hold and Maintain”, so the suitable strategy to be applied is the market penetration strategies and product development startegies. Implementation of the strategy consist of implementation of management strategies, organizational strategies of human resources, operational strategies, and financial strategies.